Odpowiedzi

2010-03-06T19:26:33+01:00
Mamy
a1 +(a1+r) +(a1 +2r)+(a1 + 3r)+(a1 +4r) + (a1 +5r) +(a1 +6r) = 147
a1 + 6r = 6*a1
------------------------------
7 a1 + 21 r = 147
6 a1 - a1 = 6r
-------------------
a1 + 3 r = 21
5 a1 = 6 r -----> r = (5 a1)/6
------------------------------------
a1 + 3*( 5 a1)/ 6 = 21
6a1 + 15 a1 = 126
21 a1 = 126
a1 = 6
--------
r = (5*6)/6 = 5
zatem mamy
a1 = 6
a2 = 6 + 5 = 11
a3 = 11 +5 = 16
a4 = 16 +5 = 21
a5 = 21 +5 = 26
a6 = 26 +5 = 31
a7 = 31 +5 = 36
Odp.
147 = 6 +11 + 16 + 21 +26 + 31 + 36
3 5 3